If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2n=n-13
We move all terms to the left:
2n-(n-13)=0
We get rid of parentheses
2n-n+13=0
We add all the numbers together, and all the variables
n+13=0
We move all terms containing n to the left, all other terms to the right
n=-13
| 19-18z=-14-15z | | -2y+3(y-1)y=-1 | | 4n−40=−14n+14 | | 8x²+16x+8=0 | | 7+2w=17 | | 0.40m+22=0.20m+28 | | 5(2^x)=55 | | 2 = q/4– 1 | | 10-4u+4=-u-10 | | 4m^2-7m=0 | | y=6×-12 | | 5-2t=-5t+2 | | -2y=-4+8 | | 2p+18=34 | | 7x+x/2=22 | | 0=8x²+16x+8 | | 2x2=72 | | -8x+9=2(13-4x)-17 | | x1/6=4/18 | | 4=10-3g | | (n+1)²-n²=61 | | 2x-43=32-3x | | (x)(x)=289 | | -105-4x=50+x | | 3(2x+4)4x=10 | | x-1/6=4/18 | | 2/3+x=180 | | 1+13+16x=1234567890 | | h=35=15 | | x+0.5=15 | | (5x+2)/8=7 | | 54=3(2x+4) |